2014
DOI: 10.1111/fwb.12367
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal movements of crayfish in a fluctuating wetland: implications for restoring wading bird populations

Abstract: 1. Among aquatic fauna of fluctuating wetlands, seasonal interhabitat movement is a widespread phenomenon that can strongly influence predator-prey interactions and population dynamics of vertebrate predators. For example, movements increase the availability of small fishes during seasonal drying, which is critical to the reproductive success of many wading bird (Ciconiiformes) species. However, few studies have examined movements of aquatic fauna in relation to changes in water depth, especially for those tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Observations from a stronger uncontrolled drought in a subsequent year substantiated this observation as crayfish burrows were common in wetland sediments (N. J. Dorn, personal observation). When partially drying the same wetlands in a previous study, Cook et al (2014; M. I. Cook, personal observation) did not find crayfish disproportionately using deep alligator holes, suggesting that most crayfish stay in the wetlands and burrow rather than move to the deepest habitats where fish are concentrated. Although difficult to quantify at this scale, crayfish likely experienced some immediate stock losses to the drying caused by the stress of burrowing (Dorn and Volin 2009) and exposure to wading bird predation (Boyle et al 2014).…”
Section: Discussionmentioning
confidence: 70%
“…Observations from a stronger uncontrolled drought in a subsequent year substantiated this observation as crayfish burrows were common in wetland sediments (N. J. Dorn, personal observation). When partially drying the same wetlands in a previous study, Cook et al (2014; M. I. Cook, personal observation) did not find crayfish disproportionately using deep alligator holes, suggesting that most crayfish stay in the wetlands and burrow rather than move to the deepest habitats where fish are concentrated. Although difficult to quantify at this scale, crayfish likely experienced some immediate stock losses to the drying caused by the stress of burrowing (Dorn and Volin 2009) and exposure to wading bird predation (Boyle et al 2014).…”
Section: Discussionmentioning
confidence: 70%
“…However, this does not imply that crayfish do not respond to receding water. A recent study by Cook et al (2014) found the slough crayfish (Procambarus fallax) moves into sloughs as water recedes off ridges, with maximum abundance occurring at~21 cm. Once depths recede <20 cm, the slough crayfish is more likely to burrow, rather than continue to follow the drying-front.…”
Section: Additional Biological Insights From Hydrological Modelsmentioning
confidence: 99%
“…As water depth declines during the dry season, prey densities increase in the sloughs as prey move downgradient within and between habitats (Kushlan , Cook et al. , Botson et al. ).…”
mentioning
confidence: 99%
“…Aquatic prey are generally expected to move downgradient across the ridge‐slough habitat interface as water recedes in the wetlands, but movement decisions may vary among species (Cook et al. , Hoch et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation